Hyperpyrexia After Rectal Misoprostol Administration-A Rare Side Effect of Misoprostol: Case Report: Misoprostol and Hyperpyrexia - Mirzamoradi, Masoumeh; Parsa, Yekta (Novelty in Biomedicine, 2022)
Background: Misoprostol is a safe drug that is one of the prostaglandins analogs. It has uterotonic solid potential and is good for postpartum hemorrhage (PPH). Misoprostol has some side effects; hyperpyrexia is a rare side effect after misoprostol administration. Cases Report: A 21-year- woman, Gravid 1 Parity 1, 18 hours after cesarean section, suffered from uterus atony and vaginal bleeding that rectal misoprostol was administered. Her PPH was managed with misoprostol and other uterotonics. She developed a fever, and because of the Coronavirus disease (covid-19) pandemic, we suspected it and assayed it, but it was negative. Conclusion: In this rare case, hyperpyrexia occurred after rectal misoprostol administration because of dose and prostaglandin effect on the hypothalamus. In this critical situation that covid-19 is pandemic, we suggest to specialists that keep in mind fever and hyperpyrexia may occur consequently the misoprostol administration.